2022
DOI: 10.3390/toxics10020095
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Particle Swarm Optimization Based In-Situ Prediction Model for Heavy Metals Concentration in Groundwater and Surface Water

Abstract: Limited monitoring activities to assess data on heavy metal (HM) concentration contribute to worldwide concern for the environmental quality and the degree of toxicants in areas where there are elevated metals concentrations. Hence, this study used in-situ physicochemical parameters to the limited data on HM concentration in SW and GW. The site of the study was Marinduque Island Province in the Philippines, which experienced two mining disasters. Prediction model results showed that the SW models during the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…The smallest mean CDI for adults was observed for Mn for all DW samples. The study of de Jesus et al (2021) in Marinduque also revealed high concentrations of Pb in the GW samples [58]. The HQ indices of metals through water intake in the study area are elaborated in Table 9.…”
Section: Human Hr Assessmentmentioning
confidence: 82%
See 2 more Smart Citations
“…The smallest mean CDI for adults was observed for Mn for all DW samples. The study of de Jesus et al (2021) in Marinduque also revealed high concentrations of Pb in the GW samples [58]. The HQ indices of metals through water intake in the study area are elaborated in Table 9.…”
Section: Human Hr Assessmentmentioning
confidence: 82%
“…The smallest mean CDI for adults was observed for Mn for all DW samples. The study of de Jesus et al (2021) in Marinduque also revealed high concentrations of Pb in the GW samples [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As cities grow and more chemical factories move away, so do the number of contaminated sites and the types of contaminants. A contaminated site is one of the current study hotspots, such as the distribution characteristics [ 1 , 2 , 3 ], risk assessment [ 4 , 5 ], remediation [ 6 , 7 , 8 , 9 , 10 ], and impact on human health [ 11 , 12 ]. Due to the typical characteristics of hidden, irreversible, and complex contaminated sites in China [ 13 ], a contaminated sites investigation has received more attention.…”
Section: Introductionmentioning
confidence: 99%
“…Three articles focus on the examination of soil contamination [ 4 , 5 , 6 ] and the possible translocation of the pollutants from soil to plants [ 7 ], and the rest focus on surface and groundwater quality [ 8 , 9 , 10 ].…”
mentioning
confidence: 99%